Pobreza y repercusión en el abandono y el maltrato de los niños betuneros del Terminal Terrestre. Cuenca, 1995-1996 - Cornejo, Sandra; Quito, Lilian; Perguachi, Carmen; Santacruz, María; León, Aida (2014)
Licenciado en Enfermería